Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1192/bjp.2021.105
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcomes of eating disorders during the COVID-19 pandemic

Abstract: Summary There are concerns that eating disorders have become commoner during the coronavirus disease 2019 (COVID-19) pandemic. Using the electronic health records of 5.2 million people aged under 30, mostly in the USA, we show that the diagnostic incidence was 15.3% higher in 2020 overall compared with previous years (relative risk 1.15, 95% CI 1.12−1.19). The relative risk increased steadily from March 2020 onwards, exceeding 1.5 by the end of the year. The increase occurred solely in females, and primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
125
3
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(147 citation statements)
references
References 10 publications
(14 reference statements)
16
125
3
3
Order By: Relevance
“…One noteworthy paper studied the electronic health records of 5.2 million people from the United States to compare the outcomes of eating disorders pre versus during the pandemic period (Taquet et al, 2021 ). The diagnostic incidence was 15% higher in 2020 compared to 2019, and the increased risk of eating disorders during the pandemic was limited to females, greatest for 10–19 year olds, and mostly affected anorexia nervosa diagnoses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One noteworthy paper studied the electronic health records of 5.2 million people from the United States to compare the outcomes of eating disorders pre versus during the pandemic period (Taquet et al, 2021 ). The diagnostic incidence was 15% higher in 2020 compared to 2019, and the increased risk of eating disorders during the pandemic was limited to females, greatest for 10–19 year olds, and mostly affected anorexia nervosa diagnoses.…”
Section: Resultsmentioning
confidence: 99%
“…The diagnostic incidence was 15% higher in 2020 compared to 2019, and the increased risk of eating disorders during the pandemic was limited to females, greatest for 10–19 year olds, and mostly affected anorexia nervosa diagnoses. Compared to those diagnosed with an eating disorder prior to the pandemic, those diagnosed during the pandemic were at a significantly higher risk of attempting suicide and having suicidal ideation (Taquet et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…3 Attempts have therefore been made to stratify clinical groups into putative biological entities, often using circulating biomarker concentration thresholds for classification. There are nonetheless examples of stratified well-powered studies testing anti-cytokine monoclonal antibodies, such as infliximab for bipolar depression 4 and sirukumab in unipolar depression, 5 that have also struggled to find a benefit, despite the clear disease-modifying actions of these treatments in prototypical inflammatory diseases.…”
Section: *Stephan Zipfel Ulrike Schmidt Katrin E Gielmentioning
confidence: 99%
“…Multiple reports from different countries, in Europe, Australia, and North America, have shown an increase in the incidence of eating disorder behaviours or diagnoses in the community, or deterioration of eating disorders in patient populations, often with more severe symptoms and comorbidities since the start of the COVID-19 pandemic. Using electronic health records of 5·2 million young people, Taquet and colleagues 4 demonstrated that the overall incidence of eating disorders increased during the COVID-19 pandemic by 15·3% in 2020, compared with previous years. The relative risk of eating disorders increased steadily from March, 2020, onwards, exceeding 1·5 by the end of the year.…”
mentioning
confidence: 99%
“…Taking such actions seems to be important in the light of reports which show that disordered eating can intensify over time and lead to the development of a full syndrome of eating disorders [ 47 ]. And, as recent research shows, the problem of eating disorders has increased significantly during the COVID-19 pandemic, which was also associated with a higher percentage of patients in this group having suicidal ideation and attempting suicide [ 48 ].…”
Section: Discussionmentioning
confidence: 99%